Influence of acrylamide on ROS, Hsp27 and NF-kB in bone marrow mesenchymal stem cells - LIU, YANG; TAO, XIAOLI; MU, YULIAN; WANG, PAN; FENG, SHUTANG; LI, KUI (The Indian Journal of Animal Sciences, 2016)
The bone marrow mesenchymal stem cells (BM-MSCs) treated with acrylamide (ACR) were used to make out the immune response to ROS, interleukin-8 and phosphorylated Hsp27 of ACR. ACR was reported as a probable human carcinogen, neurotoxic and mutagenic. BMMSCs have the capability of immunoregulation, and participate in the process of multiple immune response. It has attracted the attention of researchers that these cells have priority to move to the damaged tissue, as a kind of potential therapeutic tool for tissue repair. ACR and BMMSCs are related to immune reactions, especially those involving in tumours and cancers. However, the interaction between ACR and BMMSCs is still poorly understood. In present study, we report the influence of ACR on BMMSCs. At first, BMMSCs were disposed with 0.5mM ACR for 72 h, and then the secretion of ROS, interleukin-8, phospho- Hsp27 and NF-kB activities, apoptosis and cell cycle, respectively, were determined. The results showed that the secretion of ROS, interleukin-8 and phosph-Hsp27 increased and NF-kB was activated, while the apoptosis and cell cycle have no obvious alteration. In conclusion, ACR probably activated the NF-kB pathway in BMMSCs via oxidative stress, which may provide new insights to study the immune response and the influence mechanism of ACR.